European Reference Network eUROGEN guidelines on the management of anorectal malformations, part II: treatment - Aubert, Ophelia; Irvine, Willemijn F. E.; Aminoff, Dalia; Baauw, Ivo de; Cascio, Salvatore; Cretolle, Célia; Iacobelli, Barbara Daniela; Mantzios, Konstantinos; Midrio, Paola; Miserez, Marc; Sarnacki, Sabine; Schmiedeke, Eberhard; et al. (European journal of pediatric surgery, 2024)
Introduction Anorectal malformations (ARMs) are rare birth defects affecting the anorectum and oftentimes the genitourinary region. The management of ARM patients is complex and requires highly specialized surgical and medical care. The European Reference Network eUROGEN for rare and complex urogenital conditions aimed to develop comprehensive guidelines for the management of ARM applicable on a European level. Methods The Dutch Quality Standard for ARM served as the basis for the development of guidelines. Literature was searched in Medline, Embase, and Cochrane. The ADAPTE method was utilized to incorporate the newest available evidence. A panel of 15 experts from seven European countries assessed currency, acceptability, and applicability of recommendations. Recommendations from the Dutch Quality Standard were adapted, adopted, or rejected and recommendations were formed considering the current evidence, expert opinion, and the European context. Results Surgical and medical treatment of ARM, postoperative instructions, toilet training, and management of fecal and urinary incontinence were addressed. Seven new studies were identified. The panel adapted 23 recommendations, adopted 3, and developed 8 de novo. The overall level of newly found evidence was considered low. Conclusion Treatment of ARM patients requires a multidisciplinary team and expertise about anatomical and surgical aspects of the disease, as well as long-term follow-up. This guideline offers recommendations for surgical and medical treatment of ARM and associated complications, according to the best available evidence and applicable on a European level.
Artikel online veröffentlicht: 19. September 2024
Gesehen am 07.01.2025